The automatic rubber seed clone identification are presented using reflectance sensor, LDR and PIC: article - Azman, Siti Harishah (2012)
The automatic rubber seed clone identification are presented using Reflectance sensor, LDR and PIC as a controller. The objective of this project is to create an intelligent and automatic identification of rubber seed using application of Microcontroller PIC 16F877A. The functions of this project are to recognize of the selected best rubber three series by using the reflectance at the surface of rubber seed. This project need to identification of five type rubber seed clone. There are RRIM 2020, RRIM 2002, RRIM 2024, RRIM 2015, and RRIM 2023. The LDR are function as a detection of light because the reflectance sensors need the enough light to operate proper to recognize the surface of rubber. The reflectance sensor (QTR1A) are use to recognize the surface of rubber skin and take the sample of reading. In this project, three of reflectance are use to cover up the surface of rubber skin because the sensor is too small and cannot cover the all surface of rubber skin. These sensors also use to measure the percentage of light reflectance from seed surface. There have two distances measure the rubber seed. There are 6 mm and 1 mm from sensor to rubber seed. The Microsoft Office Excel is use to analyse the average ADC value and the voltage that cover from sensors. All rubber seed clone needs to take 25 sample of reading to do analysis. The analyses are show in TABLE and graph and decided to take the average range as a conclusion to compare the type of every clone.